Autonomous lights detecting and reporting robots from e-scrap (Scrapines). Issue 30 (2018) - Bula, Ines; Hoxha, Valmir; Hajrizi, Edmond
Abstract: Electronic Scrap (E-scrap) encompasses a broad and growing range of electronic devices ranging from large household appliances such as refrigerators, air conditioners, hand-held cellular phones, personal stereos, and consumer electronics to computers. The reuse of E-scrap is mainly limited in the separation of valuable materials, but there is another opportunity in using the E-scrap, to build robots, which are cost effective and building them can be can be very functional for different universal needs such as in a University. Autonomous lights detecting and reporting robot from e-scrap (Scrapines) is able to move through certain university spaces/classes using motion motors, to identify obstacles ultrasonic sensors are used, to detect lights in certain university spaces/classes light sensors and LDR sensors are used, robotic arm are used to turn off lights, and going back to reception to give a report which classes have been visited and in which classes lights are turn off. Autonomous detecting lights and reporting robots from e-scrap will provide a very good learning experience and also serve as a gateway to get into building robotics from e-scrap.